The Production Cost Analysis Of Agricultural Commodities On The Slopes Of Gunung Ciremai National Park - Dikdik Harjadi; Novi Satria Pradja; Nurdin Nurdin; Egi Saripudin Pratama; Irfan Aprilianto Suhara; Muhamad Akmal Sayidul Fadillah (IAIN Syekh Nurjati Cirebon, 2023)
Agriculture is one of the important sectors in Indonesia, so it needs special attention from the government. However, farmers often face several problems such as low prices at harvest, so they experience losses and do not know for sure the costs that have been incurred during the production process. This study aims to analyze the production costs of agricultural commodities on the slopes of Gunung Ciremai National Park. The collection was done by interviewing the farmers about the components and the amount of costs incurred during production. Research has found that the average cost of all commodities is Rp. 6,921,104.00 (S = 8,265,418.07; n = 230). The commodity with the highest cost was potatoes (Rp. 13,703,868.00) and the lowest was celery (Rp. 1,562,000). Celery is also the type that has the highest efficiency value (10.24), then eggplant (3.62), chili (3.52), and cabbage (2.92); while the potato is 1.55. The types that provide the largest net income are chili (Rp. 16,286,592,00) and celery (Rp. 14,550,500.00). This study also shows that celery is more suitable to be developed for farmers who have limited capital, while potatoes are for farmers with large capital. Keywords: agriculture, ciremai mountain, production costs, vegetables